2006
DOI: 10.1007/s10461-006-9174-7
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefited from an Efficacious Intervention for Youth Living with HIV: A Moderator Analysis

Abstract: An efficacious intervention that results in young people living with HIV (YPLH) reducing their transmission risk has been identified. The present study identifies who is most likely to benefit from the intervention. Regression models were used to examine whether background contextual factors moderated the intervention's success. Percentage of protected sex was moderated by ethnicity, use of antiretroviral medications (ARV), healthcare utilization and mental health. Number of partners was moderated by anxiety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…This having been said, these conclusions pertain to group data and do not rule out these possibilities in individual cases. Moreover, the association between entry CD4% and depression clearly warrants further study, to include continuing research into relations (and interactions) of youth depression with adherence 28,31,72 ; parenting behavior 73 ; caregiver depression 19,58 and HIV status 74 ; disclosure of HIV status 71 ; substance use 19,26 ; risky sexual behavior 19,22 ; social and academic functioning; and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…This having been said, these conclusions pertain to group data and do not rule out these possibilities in individual cases. Moreover, the association between entry CD4% and depression clearly warrants further study, to include continuing research into relations (and interactions) of youth depression with adherence 28,31,72 ; parenting behavior 73 ; caregiver depression 19,58 and HIV status 74 ; disclosure of HIV status 71 ; substance use 19,26 ; risky sexual behavior 19,22 ; social and academic functioning; and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Lightfoot and colleagues (2007) used regression models to examine whether background contextual factors moderated the success of an intervention for youth living with AIDS. Their findings have important implications for deciding what kind of an intervention is appropriate and beneficial for an individual young person living with AIDS (Lightfoot, Tevendale, Comulada, & Rotheram-Borus, 2007). The present study adds to this body of literature by showing that intervention effects of a couple-focused HIV prevention program on one partner's behavior may be modified by the other partner's baseline attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…There are now a number of studies that have identified important predictors of the behavioral health risks assessed in this paper, including cognitive function, 51,52 caregiver supervision and monitoring, [53][54][55] caregiver mental health, 11,56 and parent-child relationship factors, 11,[55][56][57] many of which could be targeted in these services. To date, only a few efficacy-based interventions have been developed that target caregiver-child relationship factors as well as supervision and monitoring to support mental health and reduce risk behavior in PHIV + youth and youth living with HIV + caregivers, 39,58 as well as nonadherence in PHIV + youth 39,59 and none of the interventions developed for PHIV + youth have been tested in large scale randomized control trials. Further study using prospective cohorts may be necessary to identify specific psychosocial mediators among older youth that could be targeted in interventions for multiple behavioral health risks among adolescent children of HIV-infected women, particularly HIV-infected adolescents.…”
Section: Mellins Et Almentioning
confidence: 99%